2008
DOI: 10.1086/587502
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Structure in Cosmological Simulations. I. Correlation to Observables, Mass Estimates, and Evolution

Abstract: We use Enzo, a hybrid Eulerian AMR/N-body code including nongravitational heating and cooling, to explore the morphology of the X-ray gas in clusters of galaxies and its evolution in current generation cosmological simulations. We employ and compare two observationally motivated structure measures: power ratios and centroid shift. Overall, the structure of our simulated clusters compares remarkably well to low-redshift observations, although some differences remain that may point to incomplete gas physics. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
120
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(145 citation statements)
references
References 46 publications
24
120
1
Order By: Relevance
“…This result is consistent with earlier analysis in this direction, by e.g. Jeltema et al (2008), who however found a dependence on the dynamical state once the scaling relations are not compared against the true mass but against, e.g., the hydrostatic mass. This is very plausibly the case for our simulations as well, since the hydrostatic mass bias can be large close to R500c (see our analysis in Section 3.3).…”
Section: X-ray Observablessupporting
confidence: 93%
“…This result is consistent with earlier analysis in this direction, by e.g. Jeltema et al (2008), who however found a dependence on the dynamical state once the scaling relations are not compared against the true mass but against, e.g., the hydrostatic mass. This is very plausibly the case for our simulations as well, since the hydrostatic mass bias can be large close to R500c (see our analysis in Section 3.3).…”
Section: X-ray Observablessupporting
confidence: 93%
“…One -the so-called power ratio method -is based on a multipole analysis of the azimuthal surface brightness distribution (Buote & Tsai 1995Buote 2002;Jeltema et al 2005Jeltema et al , 2008Valdarnini 2006). The other method is based on studying the emission centroid shift as a function of the integration radius (Mohr et al , 1995Poole et al 2006;O'Hara et al 2006;Kay et al 2007;Ventimiglia et al 2008;Yang et al 2008;Maughan et al 2008).…”
Section: Image Analysis and Scalingmentioning
confidence: 99%
“…Mohr et al 1993Mohr et al , 1995Poole et al 2006;O'Hara et al 2006) and the determination of so-called power ratios (e.g. Buote & Tsai 1995Jeltema et al 2005Jeltema et al , 2008Valdarini 2006;Ventimiglia et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One should, however, keep in mind that the characterization of the degree of relaxation of clusters through X-ray morphology is limited by projection effects (e.g. Jeltema et al 2008) and that the limited amount of information available at large cluster radii, beyond 0.2 R 180 , provides a further complication. There have been some attempts to compare dynamical and core properties on individual objects (e.g.…”
Section: Introductionmentioning
confidence: 99%